KEY COMPONENTS OF SOCIAL POLICY FOR ORPHANS AND CHILDREN DEPRIVED OF PARENTAL CARE - Vyshnovetska, Svitlana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: in the comparative aspect, to identify the key components of social policy for orphans and children deprived of parental care and to define its main trends in the modern times. Research methods: documentary analysis and synthesis, comparative analysis, cognitive and analytical, as well as methods of systematization and generalizations. Results: problematic aspects of Ukraine’s social policy for orphans and children deprived of parental care are analysed. Discussion: an author defend the position that they need a systematic approach to ensure the effective implementation of social policy for orphans and children deprived of parental care. Today, in the conditions of the war in Ukraine, researching the social policy for such a vulnerable category of the population as orphans and children deprived of parental care becomes especially relevant. In the research area, social policy is considered as a system consisting of seven main components. The author concluded a systematic approach, which provides for the consideration of social policy for orphans and children deprived of parental care, as a complex, multifaceted phenomenon, will ensure its integrity. The main advantage of a systematic approach in the study of these problems is that it allows to cover not only the main, but also all the accompanying phenomena and, thus, to establish and analyse the whole process of social policy in this area, to establish the relations of its key components. Regarding the problematic aspects of the research problem it is urgent to ensure the clarity of legal regulation, eliminate differences in the interpretation of basic terms, resolve law enforcement, as not all regulations on social protection of this category of children are accompanied by the implementation mechanism that prevents their implementation and makes declarative. The main trend characteristic for Ukraine, as well as for the EU countries, is the focus of social policy on the deinstitutionalization of orphans and children deprived of parental care. At the same time, the deinstitutionalization of orphanages is associated not only with the disbandment or reform of existing social institutions, changes in their organizational and legal status, but also with changes in the organization of activities and programs of social education, preparing them for further independent life. The potential results of the deinstitutionalization policy are expressed not only in the reduction of the number of orphans in orphanages, but also in the construction of a new system of social relations and social education system within the existing social institutions.